2020
DOI: 10.3390/jpm10030115
|View full text |Cite
|
Sign up to set email alerts
|

The Other Side of Alzheimer’s Disease: Influence of Metabolic Disorder Features for Novel Diagnostic Biomarkers

Abstract: Nowadays, the amyloid cascade hypothesis is the dominant model to explain Alzheimer’s disease (AD) pathogenesis. By this hypothesis, the inherited genetic form of AD is discriminated from the sporadic form of AD (SAD) that accounts for 85–90% of total patients. The cause of SAD is still unclear, but several studies have shed light on the involvement of environmental factors and multiple susceptibility genes, such as Apolipoprotein E and other genetic risk factors, which are key mediators in different metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 352 publications
(436 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, it has been shown that genetic variations of the gene encoding the CYP2C8 drug metabolizing enzymes can lead to clinical differences in drug metabolism and ultimately variations in drug effectiveness and toxicities within populations in the same country. This is observed in different populations living in Jordan [ 21 ], which include Chechens (~1%) and Circassians, genetically isolated groups [ 22 , 23 ]. Chechens display several pharmacogenomics variants (i.e ABCB1 , VDR ) resembling those present in Europeans and Finnish [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that genetic variations of the gene encoding the CYP2C8 drug metabolizing enzymes can lead to clinical differences in drug metabolism and ultimately variations in drug effectiveness and toxicities within populations in the same country. This is observed in different populations living in Jordan [ 21 ], which include Chechens (~1%) and Circassians, genetically isolated groups [ 22 , 23 ]. Chechens display several pharmacogenomics variants (i.e ABCB1 , VDR ) resembling those present in Europeans and Finnish [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, evidence has accumulated demonstrating how the physico-chemical properties of the cellular microenvironment, as well as the physical forces exerted by cells and tissues, are critical in the regulation of physiological conditions (such as tissue development, repair, and homeostasis, cell motility, proliferation, metabolism and differentiation) (Mammoto and Ingber 2010 ; Morena et al 2017 , 2020 ; Argentati et al 2018 , 2019 ; Wolfenson et al 2019 ) but also pathological states (Jansen et al 2015 ; Jensen et al 2015 ; Alcaraz et al 2018 ; Kim et al 2019 ; Lee et al 2019 ; Argentati et al 2019 , 2020b ; Hall et al 2020 ). In both contexts, cells must adapt their behavior using their capability to sense the external physical forces— mechanosensing —and to transduce these forces into biochemical signals— mechanotransduction (Trubelja and Bao 2018 ; Martino et al 2018 ; Argentati et al 2019 ).…”
Section: Organoids and Mechanobiologymentioning
confidence: 99%
“…Besides genetically determined factors, in addition to acute environmental factors, all people experience age-related changes in blood vessels over time, which can become an independent cause of neurodegenerative diseases. The main diseases, in terms of scale and worldwide distribution, are senile dementia of the Alzheimer's type or sporadic Alzheimer's disease (SAD) which accounts for 85-90% of total patients [8][9][10]. Further, an important emerging avenue in dementia research is understanding the vascular contributors to dementia.…”
Section: Introductionmentioning
confidence: 99%